THE USE OF DISCOURSE MARKERS IN SPEECHES OF THE PAKISTAN NATIONAL ASSEMBLY FROM 2002 TO 2020: A CORPUS-BASED STUDY - Muhammad Shoaib Tahir; Minnaa Ahmad; Namra Fazal; Mahnoor Amjad (International Journal of Contemporary Issues in Social Sciences, 2024)
This thesis entitled “The Use of Discourse Markers in Speeches of the Pakistan National Assembly from 2002 to 2020: A Corpus-Based Study” explains about discourse markers in speeches of Pakistan National Assembly. In analyzing the research problems, the writer uses Fraser’s theory (1999), the purpose of this thesis is to find out discourse markers in the speeches of Pakistan National Assembly. The method of research that is used in this thesis is qualitative method and the finding of this study that is there are 3 kinds of discourse markers in 20 speeches of Pakistan National Assembly. Marker of connective and (and as a discourse coordinator, and as a continuation unit of speaker, and as a service of a more general point), marker but, and marker or. In twenty speeches of Pakistan National Assembly there are three discourse markers which are not found in twenty speeches (twenty years), they are Contrastive markers (In contrast) – (on the other hand).